2019
DOI: 10.3390/coatings9020082
|View full text |Cite
|
Sign up to set email alerts
|

Verification Study of Nanostructure Evolution with Heating Treatment between Thin and Thick Fullerene-Like Hydrogen Carbon Films

Abstract: Fullerene-like hydrogen carbon films with a thin film grown on a NaCl substrate are usually employed to show the nanostructure of films (usually of hundred nanometers thick grown on Si substrates) under high resolution transmission electron microscopy (HRTEM) tests because it is easier floated off, where dependability and reasonability has never been seriously contested. Thus, in this paper, thin and thick hydrogen carbon films have been deposited on NaCl (thin films) and Si (thick films) substrates and anneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…The result of the H content is calculated by the following equation where m is the slope of the Raman spectrum. The H atom content of the a-C:H film ranges from 21–23 atom %, which is in accordance with our previous reports . Thus, in the present study, it can be assured that annealing has a negligible impact on the desorption of H atom .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The result of the H content is calculated by the following equation where m is the slope of the Raman spectrum. The H atom content of the a-C:H film ranges from 21–23 atom %, which is in accordance with our previous reports . Thus, in the present study, it can be assured that annealing has a negligible impact on the desorption of H atom .…”
Section: Resultssupporting
confidence: 93%
“…The H atom content of the a-C:H film ranges from 21−23 atom %, which is in accordance with our previous reports. 28 Thus, in the present study, it can be assured that annealing has a negligible impact on the desorption of H atom . In addition, the sp 2 carbon cluster size (L a ) could be calculated by the following formula…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…It can be concluded that the composition of all samples studied in the present work are nearly unchangeable. Both the lowest C and the highest O composite are present in T3 but the Ti/(Ti + C + O) ratio keeps constant until the target current increases to 1.10 A, where the Ti content increases to about 40 at.% (Table 2), which can be assigned to the sputtering modes variation from transition to metal mode [45,46] and the O/(Ti+C+O) ratio fluctuation can be ascribed to the contamination of the oxygen from open atmosphere during transportation [26,27,29]. Thus, it can be confirmed that the composition has no influence on the friction and anti-corrosion properties.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that reactive magnetron sputtering technology is a useful way to grow low friction solid films, such as TiN x , CrN x , TiC x and CrC x films and diamond-like carbon films as well as fullerene-like hydrogen carbon films [18][19][20][21][22][23][24][25][26], which show not only low friction or even superlubricity but also high anti-corrosive properties via magnetron sputtering method [27][28][29][30][31]. Further, the so-called metallic oxycarbides MeO x C y , produced by magnetron sputtering, have attracted the interest of materials scientists.…”
Section: Introductionmentioning
confidence: 99%